2023
DOI: 10.3390/app13106333
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Crack Growth in Nanostructured Quasi-Brittle Materials Governed by Second Gradient Elastodynamics

Abstract: The elastodynamic stress field near a crack tip propagating at a constant speed in isotropic quasi-brittle material was investigated, taking into account the strain gradient and inertia gradient effects. An asymptotic solution for a steady-state Mode-I crack was developed within the simplified strain gradient elasticity by using a representation of the general solution in terms of Lamé potentials in the moving framework. It was shown that the derived solution predicts the nonsingular stress state and smooth op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The cohesive effects arise naturally in SGE solutions due to more general definition of surface tractions that takes into account the balance of stresses and hyper-stresses [19][20][21]. For the problems of growing cracks it was also shown that gradient theories allow to describe the stabilizing and crack tip shielding effects [22][23][24] in quasi-brittle materials. Implementation of SGE models in the advanced numerical methods allowed to obtain the refined and mesh-independent solutions for the problems of crack propagation [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The cohesive effects arise naturally in SGE solutions due to more general definition of surface tractions that takes into account the balance of stresses and hyper-stresses [19][20][21]. For the problems of growing cracks it was also shown that gradient theories allow to describe the stabilizing and crack tip shielding effects [22][23][24] in quasi-brittle materials. Implementation of SGE models in the advanced numerical methods allowed to obtain the refined and mesh-independent solutions for the problems of crack propagation [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%